Relação entre os títulos de anticorpos anti LDLox e marcadores do risco cardiovascular - Santos, Andreza Oliveira dos [UNIFESP] (2008)
Objectives: Oxidized lipoproteins and antibodies anti-oxidized LDL (anti-oxLDL) have been detected in human plasma and in atherosclerotic lesions. However, the role of these autoantibodies in the maintenance of health or in the pathogenesis of acute coronary syndromes (ACS) remains unclear. We examined the relationship of human IgG antibodies anti- ox LDL with cardiovascular disease risk markers. Methods: Titers of human anti-oxLDL were measured in hypertensive subjects in stage 1 (n=94) without other risk factors, and in individuals with metabolic syndrome after recent acute coronary syndrome (n=116). Autoantibodies against copper ion oxidized LDL were measured by ELISA. Results: Hipertensive patients presented lower BMI, waist circunference, higher blood pressure levels than those with ACS (p<0.001). HDL-C and Apo A1 were higher, whereas triglycerides and Apo B were lower in those with hypertension stage 1 (p<0.0001). Anti-oxLDL titers were higher in hypertensive patients compared to those with acute coronary syndromes, and hypertensive patients presented lower hs-CRP than those with ACS (p<0.0001). Taken into account both populations, univariate analysis showed small, but significant inverse correlations between the hs-CRP (r=-0.284), BMI (r=-0.256), waist circunference (r=-0.368), apo B (r= -0.191), and blood glucose (r= - 0.303) and positive correlations between systolic and diastolic blood pressure (r=0.319 and r=0.167, respectively), HDL-C and Apo A1 (r=0.224 and r=0.257, respectively), with anti-ox LDL titers (p<0.02). After multiple linear regression, hs-CRP, fasting glycemia and waist circunference remained independently associated with anti-oxLDL. Conclusions: Our results suggest that low titers of circulating anti-oxLDL antibodies may be associated with increased cardiovascular risk.